Impacts of biomass burning in Southeast Asia on aerosols over the low-latitude plateau in China: An analysis of a typical pollution event - Fan, Wenxuan; Li, Jie; Han, Zhiwei; Wu, Jian; Zhang, Shuang; Zhang, Chuwei; Li, Jiawei (Frontiers in Environmental Science, 2023)
From March to April, widespread forest fires and agro-residue burning frequently occur in Southeast Asia, which release large amounts of gas species and aerosols and impact air quality over the wide source and downwind regions. In this study, we investigated the impact of biomass burning (BB) over Southeast Asia on particulate matter (PM) concentrations and aerosol properties in downwind areas of the low-latitude plateau from 1 March to 30 April 2019, with a focus on a typical pollution event in Kunming (KM), the capital of Yunnan Province, by using a wide variety of observations from the Chenggong ground monitoring station in Yunnan University (YNU), an air quality network in China, satellite retrievals and ERA-5 reanalysis data and numerical simulation. A regional pollution event contributed by BB pollutants from Southeast Asia and the India-Myanmar trough occurred in Yunnan Province on 31 March to 1 April 2019, which was the only typical pollution event that pollution transmission ran through central Yunnan Province from south to north since 2013, when the Airborne Pollution Action Plan was unveiled by China government. The daily mean PM2.5, PM1, and black carbon (BC) concentrations increased by 73.3 μg m-3(78%), 70.5 μg m-3 (80%), and 7.7 μg m-3 (83%), respectively, and the scattering and absorbing coefficients increased by 471.6 Mm-1 and 63.5 Mm-1, respectively, at the Chenggong station. The southwest winds exceeding 2 km vertically thick appeared in front of the India-Myanmar trough over the fire regions, pushing BB plumes northward into Yunnan Province. The model results show that 59.5% of PM2.5 mass produced by BB in Yunnan Province was sourced from the Myanmar-Thailand border, and 29.3% was from western Myanmar at a lower altitude (<4.9 km), which indicated that BB in the Myanmar-Thailand border was the dominant contributor.